The Assyrian Dictionary of the Oriental Institute of the University of Chicago. Vol. 14: R (1999)
Edited by Erica Reiner and Martha T. Roth, with the assistance of Jeremy A. Black, Hermann Hunger, Burkhart Kienast, Maureen Gallery Kovacs, Johannes M. Renger, Kaspar K. Riemschneider, Francesca Rochberg, and Matthew W. Stolper.